How to Become a Generalist Species? Individual Niche Variation Across Habitat Transformation Gradients - Liang, Dan; Yang, Shengnan; Pagani-Núñez, Emilio; He, Chao; Liu, Yang; Goodale, Eben; Liao, Wen Bo; Hu, Junhua (Frontiers in Ecology and Evolution, 2020)
Species in transformed habitats, frequently labelled as environmental generalists, tend to show broader niches than species in natural habitats. However, how population niche expansion translates into changes in the niches of individual organisms remains unclear, particularly in the context of habitat transformation. Niche expansion could be a product of individuals having broader niches, greater distances among individuals’ niches, or a combination of both processes. This would challenge the traditional conceptions on niche dynamics, which emphasize the role played by individual specialization (IS). Here, using stable isotopes, we computed total niche width (TNW), its within- and between-individual components (WIC & BIC), and IS (the ratio WIC/TNW), in 13 populations of 6 bird species and 8 populations of 3 frog species in natural and transformed habitats. We confirmed that species had broader niche width in transformed than in natural habitats, yet population niche expansion across habitats was mainly a product of increased distance between individuals. Within each habitat type, increases in TNW were linked to increases in WIC for all habitat types, while relationships between TNW and BIC were found in transformed but not in natural habitats. Hence, both increased individual niche width and increased distance among individuals were apparent within habitats, particularly in transformed ones, where increases in WIC dominated. Neither across or within habitats was niche expansion associated with increasing IS. Therefore, our results overturn traditional conceptions associated with the niche variation hypothesis and illustrate that niche expansion is not invariably associated with increased IS, because the distance between individual’s niches (BIC) can increase, as well as the breadth of those niches (WIC).